1996
DOI: 10.1080/07315724.1996.10718617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the oral administration of Lactobacillus brevis subsp. coagulans on interferon-alpha producing capacity in humans.

Abstract: Oral administration of live Labre significantly increased IFN-alpha production in a dose-dependent manner. Labre intake tended to be most beneficial in subjects with initially low levels of IFN-alpha production. Heat-treated Labre did not elicit a response similar to that of the live bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 31 publications
0
51
0
1
Order By: Relevance
“…The ability of probiotic LAB to stimulate the human immune system has been demonstrated in previous studies (de Simone et al, 1986Simone et al, , 1991Solis-Pereyra & Lemmonier, 1991;Link-Amster et al, 1994;Schiffrin et al, 1995;Kishi et al, 1996). In particular, dietary consumption of some strains of LAB has been shown to enhance cellular immune responses, including phagocytosis, lymphocyte proliferation and cytokine production (de Simone et al, 1986;LinkAmster et al, 1994;Schiffrin et al, 1995).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The ability of probiotic LAB to stimulate the human immune system has been demonstrated in previous studies (de Simone et al, 1986Simone et al, , 1991Solis-Pereyra & Lemmonier, 1991;Link-Amster et al, 1994;Schiffrin et al, 1995;Kishi et al, 1996). In particular, dietary consumption of some strains of LAB has been shown to enhance cellular immune responses, including phagocytosis, lymphocyte proliferation and cytokine production (de Simone et al, 1986;LinkAmster et al, 1994;Schiffrin et al, 1995).…”
Section: Discussionmentioning
confidence: 81%
“…It is well known that some strains of LAB can enhance cellular immune function, either innate or speci®c, when used as a probiotic (de Simone et al, 1986(de Simone et al, , 1991SolisPereyra & Lemmonier, 1991;Link-Amster et al, 1994;Schiffrin et al, 1995;Kishi et al, 1996). However, studies conducted to date have generally indicated a positive effect on one particular cellular function, such as phagocytosis or cytokine-secreting activity (Schiffrin et al, 1995;Kishi et al, 1996;Donnet-Hughes et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kishi et al (1996), the effect of lactobacilli on the immune system depends on the dose. A higher intake of bacteria resulting in a superior response compared with a lower intake.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that influence the immunomodulative activities of LAB: a) a wide difference in the ability of LAB to influence the immune system (Perdigón and Alvarez, 1992;De Petrino et al, 1995;Paubert-Braquet et al, 1995) b) the effect of LAB on the immune system depends on the dose (Kishi et al, 1996) c) live cultures are more efficient in some aspects of immune stimulation compared with dead bacteria (Portier et al, 1993;Vesely et al, 1995) d) LAB applied in fermented products induce higher responses compared with cells applied in non-fermented products (Perdigón et al, 1986;Saucier et al, 1992) Other factors that could influence the efficiency of LAB by stimulation of immunity are probably the age of the host, the physiological status of the host, and the quality and quantity of feeding.…”
Section: Stimulation Of the Immune System Induced By Lactic Acid Bactmentioning
confidence: 99%